The Middle English ophthalmic treatise on the use of the eye in G.U.L. MS Hunter 513 (ff. 1r-37r): An annotated edition and study. By Teresa Marqués Aguado - Antonio Miranda García - Santiago González Fernández-Corugedo (eds.) - Esteban-Segura, Laura (Studia Anglica Posnaniensia, 2010)
Review: The Middle English ophthalmic treatise on the use of the eye in G.U.L. MS Hunter 513 (ff. 1r-37r): An annotated edition and study. By Teresa Marqués Aguado – Antonio Miranda García – Santiago González Fernández-Corugedo (eds.). Málaga: Servicio de Publicaciones de la Universidad de Málaga, 2008. Pp. xvi, 253.